HEALTH EDUCATION FOCUSED ON CHILDREN'S HEALTH CARE: EXPERIENCE REPORT OF A HEALTH FAIR - Meira, Aliciane Oliveira; Porto, Alana Oliveira; Souza, Cristiane da Silva Machado; Santos, Givani Moraes; dos Santos, Lorena Silva (Editora Impacto Científico, 2025)
Objective: To report on the experience of health education focused on child growth and development at a health fair.Method: This is a descriptive, experience-based study of health education focused on important aspects of child growth and development, using the Humanescent Experiential Pedagogy methodology, conducted at a health fair.Results: Based on their experiences, participants discussed the importance of well-child visits, assessment of developmental milestones, provision of vaccines, vitamins, and nutritional supplements, and guidance on breastfeeding and the introduction of solid foods.Conclusion: Health education proved to be an important tool for health promotion and care, crucial for healthy growth and development.DOI: 10.56238/edimpacto2025.060-002